Suri pag-arok sa likhang-panitik = probing the literary text - Lumbera, Bienvenido (Diliman, Quezon City University of the Philippines Press, 2017)
History and criticism of Philippine literary works.
Includes bibliographical references.
Tagalog and English.
Keywords: Philippine literature -- History and criticism